2015
DOI: 10.1523/jneurosci.2389-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Motivation on Control Hierarchy in the Human Frontal Cortex

Abstract: The frontal cortex mediates cognitive control and motivation to shape human behavior. It is generally observed that medial frontal areas are involved in motivational aspects of behavior, whereas lateral frontal regions are involved in cognitive control. Recent models of cognitive control suggest a rostro-caudal gradient in lateral frontal regions, such that progressively more rostral (anterior) regions process more complex aspects of cognitive control. How motivation influences such a control hierarchy is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 50 publications
5
56
0
Order By: Relevance
“…This particular study showed that incentives yielded an additive increase in BOLD signal, on top of demand-driven control signals. However, more recent work has shown that incentive information is not merely additive, but interactive: with increasing incentive-related activity under high task-demand conditions, thus more directly implicating incentives in the enhancement of cognitive control (Bahlmann et al, 2015), cf. (Krebs et al, 2012).…”
Section: Motivated Cognitionmentioning
confidence: 99%
“…This particular study showed that incentives yielded an additive increase in BOLD signal, on top of demand-driven control signals. However, more recent work has shown that incentive information is not merely additive, but interactive: with increasing incentive-related activity under high task-demand conditions, thus more directly implicating incentives in the enhancement of cognitive control (Bahlmann et al, 2015), cf. (Krebs et al, 2012).…”
Section: Motivated Cognitionmentioning
confidence: 99%
“…Non-human primate studies using both lesions of the ACC and neuronal recording have demonstrated that ACC is critical for learning the value of actions (Kennerley et al, 2006; Amemori et al, 2015). An fMRI study examining the influence of motivation on the control hierarchy in the human frontal cortex found that the right anterior cingulate was one of the regions with the most significant Z max further supporting the importance of this region in motivation (Bahlmann et al, 2015). If long-term use of cannabis is associated with reduction in volume of the right anterior cingulum, the potential for changes in motivated behaviors appears to be a possibility.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies with human participants, responses in acquiring rewards and avoiding punishments were faster when participants predicted the need for greater efforts to perform the tasks [Kurniawan et al, ], and the reward‐related enhancement of a motor task under the optimal level of reward was found only when the task was difficult to complete [Chib et al, ]. Other studies have demonstrated that the enhancing effect of reward on the performance of cognitive tasks is highest when the cognitive control demands are of intermediate difficulty [Bahlmann et al, ] and that there is no reward‐related enhancement when the retrieval performance is sufficiently high in reward‐motivated memory retrieval tasks in which participants are shown reward values associated with the target stimuli just before the retrieval phase [Elward et al, ]. Taken together, the effect of reward on behavioral performance in cognitive tasks, including episodic memory, could be most effective when the task difficulty is adjusted to optimal levels, and the reward‐related enhancement of memory retrieval could be mediated by a reward‐related increase in subjective motivation at the optimal levels of task difficulty.…”
Section: Discussionmentioning
confidence: 99%